Clinical and Diagnostic (CT scan) Case Profile of Traumatic Brain Injury (TBI) Patients in a Teritiary Care Center, Visakhapatnam - A Retrospective Observational Study - Rao, V. Dharma; Kuna, Kodandarao; Patro, Mohan; S., Deepak M. (International Journal of Innovative Research in Medical Science, 2019)
Introduction: India experiences increase in incidence of Road Traffic Accidents (RTA). During 1970 to 2011, there is 7.3 times increase in road accident injuries. Head injury is the commonest due to RTA injury which accounts for 60% of cases in Visakhapatnam which is situated along the 9National Highway. Aim: The aim is to study the clinical and CT scan diagnostic case profile of Traumatic brain injury (TBI) in Visakhapatnam region. Material & Methods: It is a retrospective observational study of cases of TBI reported at the trauma care center at the tetitiary care King George Hospital (KGH), Visakhapatnam, for the period 2011 – 2018. Proper permission and clearance for the present study is duly obtained. Results & Discussion: Head injury is the commonest among traumatic injuries. CT scan is performed as the gold standard diagnostic test for head injury cases. Contusions followed by Sub arachnoid hemorrhage (SAH) and Sub dural hemorrhage (SDH) are the most common CT findings. About 25% needed ventilator support. Most common cause of death is CNS injuries (42%) followed by blood loss in 39% of cases. Conclusions: Regulated traffic control, wearing helmet and seat belt, limiting speed and avoiding L & U bends at road corners can prevent and minimise the incidence of fatal injuries.